2006
DOI: 10.4049/jimmunol.177.10.6730
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Marrow: A Reservoir for “Enhanced Effector Memory” CD8+ T Cells with Potent Recall Function

Abstract: The role of human bone marrow (BM) CD8+ T cells in the immune response to viral Ags is poorly defined. We report here the identification and characterization of a functionally enhanced effector memory CD8+ T cell population (TEM) in the BM of patients undergoing total joint replacement for osteoarthritis. These BM-derived TEM differ strikingly from correlate cells in peripheral blood (PB), expressing elevated levels of CD27, HLA-DR, CD38, CD69, and unique patterns of chemokine receptors. Interestingly, while B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 56 publications
4
55
0
Order By: Relevance
“…We observed similar frequencies of CMV-specific T cells in PB and BM in accordance with a recent study by Zhang et al [17]. Consistent with previous reports we found that the majority of CD8 + CMV-specific T cells in PB were of T Eff and T EM phenotype [10,18,19], while we could demonstrate here that a large pool of CMV-specific T CM is present in BM.…”
Section: Introductionsupporting
confidence: 93%
“…We observed similar frequencies of CMV-specific T cells in PB and BM in accordance with a recent study by Zhang et al [17]. Consistent with previous reports we found that the majority of CD8 + CMV-specific T cells in PB were of T Eff and T EM phenotype [10,18,19], while we could demonstrate here that a large pool of CMV-specific T CM is present in BM.…”
Section: Introductionsupporting
confidence: 93%
“…Therefore, vaccinated animals inoculated with IL-15 or IL-7 cytokine, at the time of minimal to absent response (W18-W26), should experience earlier re-emergence of HIV-specific CD8 ϩ T cells. 2) Subsets of HIV-specific memory CD8 ϩ T cells with strong recall function may early reside in particular anatomic compartment (e.g., bone marrow) as reported recently (33). After an extensive absence of Ag and possibly unknown signals, these cells may progressively relocate in secondary lymphoid tissues like the spleen.…”
Section: Discussionmentioning
confidence: 88%
“…In this respect, melanoma antigen-specific memory T cells are of special interest because they are known to react to antigens (including tumor antigens) faster and stronger than naive T cells by increased proliferation; they release a broader spectrum of cytokines and need less costimulation by professional antigen presenting cells (4)(5)(6). Our previous studies in breast cancer patients (7)(8)(9) as well as publications of other authors (10)(11)(12) provided strong evidence that the bone marrow (BM) is a major site for persistence of tumor-specific memory T cells with central memory (CM) and effector memory (EM) phenotype. Furthermore, the BM has been recently described as a central organ in memory T-cell migration (13).…”
Section: Introductionmentioning
confidence: 93%